2004
DOI: 10.3168/jds.s0022-0302(04)73472-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pathogen-Specific Clinical Mastitis on Milk Yield in Dairy Cows

Abstract: Our objective was to estimate the effects of the first occurrence of pathogen-specific clinical mastitis (CM) on milk yield in 3071 dairy cows in 2 New York State farms. The pathogens studied were Streptococcus spp.,Staphylococcus aureus, Staphylococcus spp., Escherichia coli, Klebsiella spp., Arcanobacterium pyogenes, other pathogens grouped together, and "no pathogen isolated." Data were collected from October 1999 to July 2001. Milk samples were collected from cows showing signs of CM and were sent to the Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
268
4
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(328 citation statements)
references
References 24 publications
(41 reference statements)
34
268
4
15
Order By: Relevance
“…The association between health and milk yield is well documented in the literature for both mastitis (Grö hn et al, 2004;Windig et al, 2005;Hagnestam et al, 2007) and lameness (Barkema et al, 1994). Genetic correlations between both health traits with milk production yield traits were all positive, indicating that animals genetically above average for yield traits were more liable to mastitis and lameness.…”
Section: Genetic Correlationsmentioning
confidence: 84%
See 1 more Smart Citation
“…The association between health and milk yield is well documented in the literature for both mastitis (Grö hn et al, 2004;Windig et al, 2005;Hagnestam et al, 2007) and lameness (Barkema et al, 1994). Genetic correlations between both health traits with milk production yield traits were all positive, indicating that animals genetically above average for yield traits were more liable to mastitis and lameness.…”
Section: Genetic Correlationsmentioning
confidence: 84%
“…The greatest economic loss due to subclinical and clinical mastitis is reduced milk yield. The magnitude of losses depend very much upon the type of infection, the stage of lactation and parity (Grö hn et al, 2004). Bar et al (2007) estimated milk losses due to mastitis including repeated cases within and across lactations.…”
Section: Genetic Correlationsmentioning
confidence: 99%
“…CM due to Klebsiella infection results in high milk losses and mortality of the affected cows (13). Antimicrobial therapy and vaccination have limited effects against Klebsiella CM (15,27).…”
mentioning
confidence: 99%
“…Total losses were estimated at 8.7 kg (for the average CFU of 'PPP' cows). Gröhn et al (2003) and Hertl et al (2014) observed a drop of >8 kg in the week following a first case of clinical mastitis due to S. aureus.…”
Section: Discussionmentioning
confidence: 99%